Sharia Card: An Alternative For Islamic Payment - Mahmud Yusuf (Islamic Economics and Business Faculty of UIN Antasari, 2022)
The formulation of the problem in this study is to narrate the sharia card as a solution for using credit cards in the community. The research method used is the library research method with content analysis as an analytical knife so that the right solution is found in drawing conclusions. To ensure the validity of the data, the researcher will use the triangulation technique of sources derived from various literatures that are relevant to the research theme. The results showed that credit cards in traditional banks, this is a method of payment for the purchase and sale of goods and services, and it is possible to pay at once or in installments up to a certain minimum amount (ba’i bit-taqsith), which is haram. To avoid it, sharia cards use Islamic principle., which is not used for transactions that are not in accordance with sharia, and does not encourage excessive consumption. The main card holder must have the financial ability to pay off on time and must not provide services that are contrary to sharia. Tujuan penelitian ini adalah untuk menganalisa eksistensi kartu syariah sebagai solusi penggunaan kartu kredit di masyarakat. Metode penelitian yang digunakan adalah metode penelitian kepustakaan dengan pendekatan content analisis untuk menemukan solusi yang tepat dalam penarikan kesimpulan. Penulis menggunakan teknik triangulasi sumber dari berbagai literatur yang relevan dengan tema penelitian untuk menjamin keabsahan data. Hasil penelitian menunjukkan bahwa kartu kredit di bank konvensional yang merupakan metode pembayaran untuk pembelian dan penjualan barang serta jasa, di mana pembayarannya dapat dilakukan sekaligus atau dicicil hingga jumlah minimum tertentu termasuk dalam kategori riba yang haram. Maka untuk menghindarinya, kartu syariah menggunakan prinsip Islam, yaitu yang tidak menyebabkan sifat konsumtif dan tidak digunakan untuk transaksi yang tidak sesuai syariah. Pemegang kartu utama harus memiliki kemampuan finansial untuk melunasi tepat waktu dan tidak boleh memberikan pelayanan yang bertentangan dengan syariah.